Boyhood and delinquency in 1920s Chicago: a sociological study of juvenile Jack-Rollers and gender - Salerno, Roger A. (McFarland & Company, Inc., Publishers, 2017)
"This study of delinquency in 1920s Chicago examines the lives of boys, many of whom spent their early years incarcerated, who survived by embracing criminal personas. Predatory masculinity emerges as a source of personal struggle, and as the basis for an array of contemporary social problems, including mass violence and suicide"--